2019
DOI: 10.5194/bg-2019-394
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ocean Deoxygenation and Copepods: Coping with Oxygen Minimum Zone Variability

Abstract: <p><strong>Abstract.</strong> Increasing deoxygenation (loss of oxygen) of the ocean, including expansion of oxygen minimum zones (OMZs), is a potentially important consequence of global warming. We examined present day variability of vertical distributions of copepod species in the Eastern Tropical North Pacific (ETNP) living in locations with different water column oxygen profiles and OMZ intensity (lowest oxygen concentration and its vertical extent in a profile). C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 66 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…A recent study by Rasse and Dall'Olmo (2019) found a permanent layer of small particles linked to microbial communities located in the upper section of the oxygen minimum layer, and they further showed that attenuation of small‐particle fluxes was equivalent or significantly higher inside the oxygen minimum layer. The layer of small particles above the oxygen minimum layer could be caused by the zooplankton fragmentation of large particles into small particles (Briggs et al, 2020; Cavan et al, 2017), as many zooplankton migrate during the day into the low oxygen core or the upper boundary of the oxygen minimum layer (Steinberg et al, 2008; Wishner et al, 2018, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Rasse and Dall'Olmo (2019) found a permanent layer of small particles linked to microbial communities located in the upper section of the oxygen minimum layer, and they further showed that attenuation of small‐particle fluxes was equivalent or significantly higher inside the oxygen minimum layer. The layer of small particles above the oxygen minimum layer could be caused by the zooplankton fragmentation of large particles into small particles (Briggs et al, 2020; Cavan et al, 2017), as many zooplankton migrate during the day into the low oxygen core or the upper boundary of the oxygen minimum layer (Steinberg et al, 2008; Wishner et al, 2018, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Biogeochemical processes in OMZs are largely driven by microbial communities associated with anaerobic metabolism (e.g., denitrification, anammox), which are highly relevant in terms of fixed nitrogen loss, as well as its impact on primary production rate, carbon sequestration, and greenhouse gas production. Vertical movements in the upper limit of the OMZ (oxycline) are expected to alter such rates (Arévalo‐Martínez et al., 2015; Jiao et al., 2014; Kalvelage et al., 2015), and also have a direct impact on most aerobic organisms through an expansion or contraction of their habitat within the upper mixed layer‐seasonal thermocline, changes in their depth distribution within the OMZ or by alterations in their patterns of diel vertical migration (Bianchi et al., 2013; Gilly et al., 2013; Wishner et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…At this depth, we recorded severely hypoxic conditions (O 2 < 22.5 µmol kg -1 ) for ~1% of the deployment time (Table 1), suggesting that even though this community is above the depth frequently associated with the upper boundary of the OMZ (450 m), it is still periodically exposed to OMZ conditions. High spatial resolution-sampling of 485 the eastern tropical North Pacific OMZ documents considerable submesoscale oxygen variability with better oxygenated holes (Wishner et al 2019); such patchiness would not be unexpected off southern California. Oxygen decreases of 0.25-0.5 µmol kg -1 year -1 have been reported for depths of 400 m (Bograd et al 2008), and if these trends continue, in 13-26 years, this depth zone may become the upper boundary of the OMZ.…”
Section: Comparing Short-term Variability Of Oxygen To Long-term Trendsmentioning
confidence: 96%